EVALUASI TINGKAT KERUSAKAN JALAN SEBAGAI DASAR PENENTUAN PERBAIKAN JALAN DI KOTA KASONGAN (STUDI KASUS : JALAN KATUNEN – TUMBANG LITING) - DASLI, DASLI; Silitonga, Sutan Parasian; Desriantomy, Desriantomy (INFO-TEKNIK, 2024)
The research results show thatthe type of damage that occurred, from the largest to the smallest, namely: Alligator Cracking with an area of 1642.10 m2 (91.76%), Potholes with an area of 109.15 m2 (6.10%), Depression with an area of 30.10 m2 (1.68%), Rovelling with an area of 4.40 m2 (0.25%), Bleeding with an area of 3.87 m2 (0.22%) ). The level of damage to the Muara Katunen – Tumbang Liting road section is based on the Bina Marga and PCI (Pvaement Condition Index) methods, namely: The Bina Marga method has a road condition value of 1.50 and a priority value of 11.50 (priority value 7 and so on or class C) and MethodsPavement Condition Index (PCI) has a PCI value of 75.06 with a very good rating (very good). The type of maintenance that can be applied to the Muara Katunen – Tumbang Liting road is routine maintenance in the form of demolition and patching using class B lats. The cost required to repair the damage that occurred on the Muara Katunen road – collapsed liting is Rp. 262.239.962